Warm Edge Kelp Populations Show Elevated Volatility to Marine Heatwaves - Jiaxin Shi; Scott Bennett; Jules B. Kajtar; Thomas Wernberg; Neville S. Barrett; Graham J. Edgar; Neil J. Holbrook (Ecology Letters, 2026)
Reliable predictions of species responses to intensifying temperature extremes are crucial for managing climate change impacts. However, limited data of species' responses to heat stress across their distribution restricts prediction accuracy. Here we analyse three‐decades of kelp abundance observations in Australia, including cool to warm‐edge populations, relative to marine heatwaves (MHWs). As MHWs intensified, changes in kelp abundances shifted from positive to negative. Warm‐edge populations displayed steeper declines in abundance change than central and cool‐edge populations under comparable MHWs. Our results support a hybrid thermal performance model, whereby thermal limits differ between populations, but performance volatility increases toward species' warm‐edge, heightening vulnerability of warm‐edge populations. Importantly, realised impacts of MHWs were evident at smaller thermal anomalies than predicted by experiments and distribution models, highlighting the importance of calibrating theoretical approaches with realised ecological change. By integrating a multi‐faceted approach, our study is generalisable for improving predictions of species' population vulnerability.

2.4–2.3 Ga granitoids of the Arrowsmith orogeny, southwestern Rae craton, Canada: Syn- and post-orogenic magmatism during a global tectono-magmatic lull - Benjamin J.C. Neil; Thomas Chacko; Larry M. Heaman; S. Andy Dufrane; Robert A. Creaser; Edith Martel; Rebecca Canam; D. Graham Pearson (Precambrian Research, 2025)

Methods for quantifying low populations of root-knot nematode (Meloidogyne spp.) in vegetable soils and their potential for use in monitoring programs to improve nematode management decisions - Graham Roy Stirling; Neil L. Wilson; Jennifer A. Cobon; Wayne T. O’Neill (Australasian Plant Pathology, 2025)

A cultivar phenology classification scheme for wheat and barley - Corinne Celestina; James Hunt; Haydn Kuchel; Felicity Harris; Kenton Porker; Ben Biddulph; Maxwell Bloomfield; Melissa McCallum; Rick Graham; Peter Matthews; Darren Aisthorpe; Ghazwan Al-Yaseri; et al. (European Journal of Agronomy, 2023)

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

A narrative review of the potential pharmacological influence and safety of ibuprofen on coronavirus disease 19 (COVID-19), ACE2, and the immune system: a dichotomy of expectation and reality - Lucinda Smart; Neil Fawkes; Paul Goggin; Graham Pennick; K. D. Rainsford; Bruce Charlesworth; Neil Shah (Inflammopharmacology, 2020)
The coronavirus disease 19 (COVID-19) pandemic is currently the most acute healthcare challenge in the world. Despite growing knowledge of the nature of Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2), treatment options are still poorly defined. The safety of non-steroidal anti-inflammatory drugs (NSAIDs), specifically ibuprofen, has been openly questioned without any supporting evidence or clarity over dose, duration, or temporality of administration. This has been further conflicted by the initiation of studies to assess the efficacy of ibuprofen in improving outcomes in severe COVID-19 patients. To clarify the scientific reality, a literature search was conducted alongside considerations of the pharmacological properties of ibuprofen in order to construct this narrative review. The literature suggests that double-blind, placebo-controlled study results must be reported and carefully analysed for safety and efficacy in patients with COVID-19 before any recommendations can be made regarding the use of ibuprofen in such patients. Limited studies have suggested: (i) no direct interactions between ibuprofen and SARS-CoV-2 and (ii) there is no evidence to suggest ibuprofen affects the regulation of angiotensin-converting-enzyme 2 (ACE2), the receptor for COVID-19, in human studies. Furthermore, in vitro studies suggest ibuprofen may facilitate cleavage of ACE2 from the membrane, preventing membrane-dependent viral entry into the cell, the clinical significance of which is uncertain. Additionally, in vitro evidence suggests that inhibition of the transcription factor nuclear factor-κB (NF-kB) by ibuprofen may have a role in reducing excess inflammation or cytokine release in COVID-19 patients. Finally, there is no evidence that ibuprofen will aggravate or increase the chance of infection of COVID-19.

The ENHANCED MAGNAPORTHE RESISTANCE 1 locus affects Ramularia leaf spot development in barley - Graham R. D. McGrann; Steven Miller; Neil D. Havis (European Journal of Plant Pathology, 2020)
Ramularia leaf spot (RLS) is a newly-important disease of barley which is caused when the fungus Ramularia collo - cygni enters necrotrophic development during colonisation of the host. Mutant alleles at the barley MILDEW LOCUS O , mlo , locus confer broad spectrum durable resistance against the powdery mildew fungus, Blumeria graminis f. sp. hordei , but can enhance susceptibility to pathogens with necrotrophic development stages such as R . collo - cygni . Given the importance of mlo in spring barley breeding programmes, identifying loci that mitigate the effect of mlo -mediated susceptibility on necrotrophic disease development is an important target. Mutation of the ENHANCED MAGNAPORTHE 1 ( emr1 ) locus which can affect mlo -associated disease susceptibility, leads to a reduction in RLS symptoms on barley leaves but does not reduce R . collo - cygni accumulation. The effect of emr1 on the transition of R . collo - cygni from endophyte to necrotroph may relate to changes in reactive oxygen species in mutant plants which show reduced sensitivity to chloroplastic superoxide induced cell death and has lower relative chlorophyll content compared to mlo plants.

Overexpression of the MYB29 transcription factor affects aliphatic glucosinolate synthesis in Brassica oleracea - Diana L. Zuluaga; Neil S. Graham; Annett Klinder; A. E. Elaine van Ommen Kloeke; Angelo R. Marcotrigiano; Carol Wagstaff; Ruud Verkerk; Gabriella Sonnante; Mark G. M. Aarts (Plant Molecular Biology, 2019)

Total and methyl-mercury seasonal particulate fluxes in the water column of a large lake (Lake Geneva, Switzerland) - Elena Gascón Díez; Neil D. Graham; Jean-Luc Loizeau (Environmental Science and Pollution Research, 2018)

Somatic mutations of the coding microsatellites within the beta-2-microglobulin gene in mismatch repair-deficient colorectal cancers and adenomas - Mark Clendenning; Alvin Huang; Harindra Jayasekara; Marie Lorans; Susan Preston; Neil O’Callaghan; Bernard J. Pope; Finlay A. Macrae; Ingrid M. Winship; Roger L. Milne; Graham G. Giles; Dallas R. English; et al. (Familial Cancer, 2018)

Control of light leaf spot and clubroot in brassica crops using defence elicitors - Graham R. D. McGrann; Tracy Yoxall; Linda J. Paterson; Jeanette M.G. Taylor; Ioannis G. Birmpilis; Dale R. Walters; Neil D. Havis (European Journal of Plant Pathology, 2017)

Understanding the double peaked El Niño in coupled GCMs - Felicity S. Graham; Andrew T. Wittenberg; Jaclyn N. Brown; Simon J. Marsland; Neil J. Holbrook (Climate Dynamics, 2017)

The influence of bottom boundary layer hydrodynamics on sediment focusing in a contaminated bay - Neil D. Graham; Damien Bouffard; Jean-Luc Loizeau (Environmental Science and Pollution Research, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

Life history and population characteristics of the Antarctic starfish, Anasterias antarctica Lütken, 1856 (Asteroidea: Forcipulatida: Asteriidae) around the Falkland Islands - Vladimir Laptikhovsky; Paul Brickle; Marta Söffker; Deborah Davidson; Marie-Julie Roux; Kalinka Rexer-Huber; Paul E. Brewin; Emma Kälkvist; Judith Brown; Steve Brown; Andy Black; Neil R. Anders; et al. (Polar Biology, 2015)

Phenological decoupling of mortality from wave forcing in kelp beds - Thibaut de Bettignies; Thomas Wernberg; Paul S. Lavery; Mathew A. Vanderklift; Jim R. Gunson; Graham Symonds; Neil Collier (Ecology, 2015)
Kelps often live in a harsh hydrodynamic environment where wave‐driven dislodgement of individuals can alter the biodiversity and functioning of reef systems, and increase production in coastal ecosystems adjacent to reefs. The current paradigm is that winter storms tear kelps from reefs once hydrodynamic forces exceed attachment or tissue strength—a threshold response that implies a pulsed relationship between wave forces and dislodgement. Here, we challenge this understanding by showing how kelp phenology can decouple susceptibility to dislodgement from seasonal patterns in wave forces. We measured kelp dislodgement rates and hydrodynamic forces at nine subtidal reefs over two years ( n = 4320 kelps tagged and monitored). Contrary to expectation, we found relatively low and constant dislodgement rates for all reefs (13% ± 6% [mean per season ± SD]) in spite of a strong temporal pattern in wave action and extreme water velocities (winter peaks up to 3–4 m/s). A biomechanical model, based on the balance between kelp attachment strength and hydrodynamic drag, demonstrated that severe reduction in individual kelp size toward winter (>50% decrease in biomass for all sites) minimized drag and made the kelps less susceptible to high water velocities, allowing individuals to survive storm velocities over 3–4 m/s. We conclude that the timing of reduced susceptibility to disturbance, through the seasonal reduction of individual kelp biomass that coincides with times of highest water velocities is critical to the dynamics of kelp dislodgement and survival. We propose that phenological processes maintain many kelp beds in a higher degree of population stability and equilibrium with hydrodynamic forces than previously believed.

Effectiveness of the Bjerknes stability index in representing ocean dynamics - Felicity S. Graham; Jaclyn N. Brown; Clothilde Langlais; Simon J. Marsland; Andrew T. Wittenberg; Neil J. Holbrook (Climate Dynamics, 2014)

Influence of a wastewater treatment plant on mercury contamination and sediment characteristics in Vidy Bay (Lake Geneva, Switzerland) - Elena Gascon Diez; Andrea Garcia Bravo; Natacha à Porta; Matthieu Masson; Neil D. Graham; Serge Stoll; Yosef Akhtman; David Amouroux; Jean-Luc Loizeau (Aquatic Sciences, 2013)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Expression of stromal genes associated with the angiogenic response are not differentiated between human tumour xenografts with divergent vascular morphologies - Matthew Farren; Susie Weston; Helen Brown; Nicola Broadbent; Steve Powell; Robert Shaw; Neil R. Smith; Rachael Inglis; Alex Graham; Sue Ashton; Stephen R. Wedge; Simon T. Barry (Angiogenesis, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

The influence of defined ante-mortem stressors on the early post-mortem biochemical processes in the abdominal muscle of the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) - Sebastian G. Gornik; Amaya Albalat; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2010)

Effect of capture method on the physiology and nucleotide breakdown products in the Norway lobster ( Nephrops norvegicus ) - Amaya Albalat; Sebastian G. Gornik; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2009)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

A possible molecular link between the toxicological effects of arsenic, selenium and methylmercury: methylmercury(II) seleno bis(S-glutathionyl) arsenic(III) - Malgorzata Korbas; Andrew J. Percy; Jürgen Gailer; Graham Neil George (JBIC Journal of Biological Inorganic Chemistry, 2008)

Responses of estuarine intertidal microphytobenthic algal assemblages to enhanced ultraviolet B radiation - JEN WARING; NEIL R. BAKER; GRAHAM J. C. UNDERWOOD (Global Change Biology, 2007)
As a result of ozone depletion, ground doses of ultraviolet B (UVB) radiation in the mid latitudes of the Northern Hemisphere have increased since the 1980s, and current predictions indicate no possible alleviation until at least post 2020. Mudflats and sandflats are important coastal‐zone habitats, and support extensive biofilms of benthic microalgae (microphytobenthos). In intertidal situations, these assemblages are exposed to high levels of UVB radiation during periods of tidal exposure. Exposure of intertidal biofilms dominated by epipelic (mud‐inhabiting) diatoms to 0, 0.18 or 0.35 W m −2 UVB radiation for between 4 and 10 days resulted in no significant decreases in the maximum PSII quantum efficiency ( F v / F m ) throughout diel exposure periods. Although the quantum efficiency of electron transport ( F q ′/ F m ′) showed significant reductions early in some experiments, the major response was an increase in F q ′/ F m ′ in UVB exposed biofilms. This increase in F q ′/ F m ′ was suggestive of a protective vertical migration down into the sediment. Single‐cell and whole biofilm fluorescence imaging demonstrated, for the first time, that motile diatoms are able to detect UVB radiation independently of UVA or photosynthetically active radiation (PAR) and migrate rapidly down (within 15 min) into the sediments to avoid it. This behavioural acclimation mechanism appears to prevent significant accumulation of UVB induced damage to the algae. UVB exposure had no significant effect of biofilm photosynthesis (measured by 14 C carbon fixation), but did alter organic carbon allocation patterns, with significantly less new carbon allocated to intracellular storage (glucan) and extracellular colloidal carbohydrate fractions. Significant reductions in the sediment standing stocks of chlorophyll a (Chl a ), colloidal carbohydrates, extracellular polymeric substances (EPS) were seen after 7 days of UVB exposure. This study showed that marine intertidal benthic diatoms use a behavioural strategy to avoid exposure to UVB and that this response is effective as a short‐term protection mechanism against UVB damage. However, altered carbon allocation patterns feed forward over time into changes in biofilm biomass and sediment carbohydrate dynamics. This suggests that continual long‐term exposure to UVB may impact on sediment carbon cycling and trophic interactions and on the stabilization of sediments by microalgal biofilms through their production of extracellular carbohydrates.

A role for manganese in superoxide dismutases and growth of iron‐deficient diatoms - Graham Peers; Neil M Price (Limnology and Oceanography, 2004)
We have discovered that coastal and oceanic diatoms require more manganese (Mn) to grow in iron (Fe) ‐deficient than in Fe‐sufficient seawater. At low inorganic concentrations, like those of the open sea, Fe and Mn can thus colimit Thalassiosira pseudonana and T. oceanica so that maximum rates of cell division are achieved only when both resources are added simultaneously to cultures. Colimited diatoms amended with either Fe or Mn alone show unique physiological responses, which implies that the observed interaction between Fe and Mn is not caused by a substitution of one metal for the other. Iron deficiency increases the Mn quota of T. pseudonana by three times compared with controls and enhances the production of reactive oxygen species by 1.7 times in T. weissflogii . Both diatoms respond to this oxidative stress by increasing the activities of the antioxidant enzyme superoxide dismutase (SOD). The Mn content of the SODs increases by 1.8 to 2.8 times when Fe is limiting, which suggests that the SODs contain Mn and may account for part of the observed increase in the Mn quota. Such an increased biochemical requirement may elevate the Mn content of low Fe diatoms, and possibly other phytoplankton, resulting in high Mn: Fe ratios in surficial particulate matter in Fe‐limited regions of the sea.

Auxin cross-talk: integration of signalling pathways to control plant development - Ranjan Swarup; Geraint Parry; Neil Graham; Trudie Allen; Malcolm Bennett (Plant Molecular Biology, 2002)

Quick on the Uptake: Characterization of a Family of Plant Auxin Influx Carriers - Geraint Parry; Alan Marchant; Sean May; Ranjan Swarup; Kamal Swarup; Nick James; Neil Graham; Trudie Allen; Tony Martucci; Antony Yemm; Richard Napier; Ken Manning; et al. (Journal of Plant Growth Regulation, 2001)

Evidence that orexin-A-evoked grooming in the rat is mediated by orexin-1 (OX 1 ) receptors, with downstream 5-HT 2C receptor involvement - Mark S. Duxon; Jennifer Stretton; Kathryn Starr; Declan N.C. Jones; Vicky Holland; Graham Riley; Jeff Jerman; Stephen Brough; Darren Smart; Amanda Johns; Wai Chan; Rod A. Porter; et al. (Psychopharmacology, 2001)

An in vitro model of angiogenesis: Basic features - Eileen T. Bishop; Graham T. Bell; Stephen Bloor; I.J. Broom; Neil F.K. Hendry; Denys N. Wheatley (Angiogenesis, 1999)